2021
DOI: 10.2174/1389202922666210225084212
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Genomics Interventions for Promoting Millets as Functional Foods

Abstract: : Several crops, including millets with immense nutritional and therapeutic values, were once a part of our regular diet. However, due to domestication and selection pressures, many of them had become marginally cultivated crops confined to a particular region, race, or locality. Millets are a perfect example of neglected species that have the potential to address both food and nutritional insecurities prevalent among the ever-growing global population. Starvation and malnutrition contribute to a large number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…This observation is attributed to high radical scavenging or quenching activity in finger millet [17,18]. Millets are a rich source of antioxidants such as curcumin, quercetin and ellagic acid which act as immune boosters, and important in the health and wellbeing of children and young adults [19]. As Millets: Traditional "Poor Man's" Crop or Future Smart Nutri-Cereals?…”
Section: Millets Contribution To Nutrition and Healthmentioning
confidence: 99%
“…This observation is attributed to high radical scavenging or quenching activity in finger millet [17,18]. Millets are a rich source of antioxidants such as curcumin, quercetin and ellagic acid which act as immune boosters, and important in the health and wellbeing of children and young adults [19]. As Millets: Traditional "Poor Man's" Crop or Future Smart Nutri-Cereals?…”
Section: Millets Contribution To Nutrition and Healthmentioning
confidence: 99%
“…The linear effect of blend ratio showed that with the increase in the blend ratio, the CP decreased (Fig 1a ) whereas the positive linear effect of curd showed that CP increased with the increase in the curd content (Fig 1b). This could be because of decrease in amount of quinoa flour from 1:1to 3:1 as the protein content of quinoa (16.89%) is more than that of finger millet (8.9%) (Dhaka and Prasad, 2020) and curd is known as excellent source of protein and contains protein with high biological value (Mckinley, 2005).…”
Section: Crude Protein (Cp)mentioning
confidence: 99%
“…Millets are also rich in polyphenols, tannins, and phytosterols and are a good source of antioxidants. Millet consumption can provide a way to eliminate nutritional deficiencies (Dhaka et al 2021).…”
Section: Introductionmentioning
confidence: 99%